Chromosomal Abnormalities in Syndromic Orofacial Clefts: Report of Three Children. (9th September 2018) - Shenoy, Rathika Damodara; Shenoy, Vijaya; Shetty, Vikram
Abstract : This case series of three children reports clinical features and chromosomal abnormalities seen in a craniofacial clinic. All presented with orofacial cleft, developmental or intellectual disability, and dysmorphism. Emanuel syndrome or supernumerary der (22)t(11; 22), the prototype of complex small supernumerary marker disorders, was seen in one child. Duplication 4q27q35.2 with concomitant deletion 21q22.2q22.3 and duplication 12p13.33p13.32 with concomitant deletion 18q22.3q23 seen in the remaining two children are not reported in literature. Maternal balanced translocation was established in both of these children.